Case Study of a New Teacher Mentoring and Induction Program - Collins, Jennifer Sarah (Concordia University (Oregon), 2018)
A single case design was employed to explore the implementation of the new teacher induction and mentoring program (NTIMP) from the perspective of new teachers who participated in the program. The district the researcher studied for this single case study had been experiencing a high teacher turnover. To reduce this problem, an NTIMP was implemented in the district. The NTIMP was investigated with a diverse sample of new educators from a semi-rural school district in the western part of the United States. Data sources, including interviews, surveys, and document review, were used in the study to allow for the triangulation of data. Findings indicated that the NTIMP was a beneficial initiative implemented by the study site for helping teachers adjust to the teaching and for reducing feelings of isolation. Responses regarding the NTIMP’s impact on a new teacher’s development of a positive attitude towards teaching and in developing a sense of professionalism indicated both positive and negative experiences. The responses to the survey questions and the semi-structured interviews reflected the importance of access to professional development and both formal and informal mentoring access for new teachers to help them achieve success in teaching. A support system is critical to new teachers who were grappling with seeking answers to questions and gathering assistance to become a more effective educator. New teachers require experienced teacher support through the development of professional relationships, relationships with students and students’ families and caregivers, and additional guidance in professional practice. Future studies should include the long-term impact of the program on participants.